Odpowiedzi

2011-06-25T01:24:03+02:00

x - y = 2
x² - 4x + y² = 0

 

x=2+y
x² - 4x + y² = 0

 

(2+y)²-4(2+y)+y²=0

4+4y+y²-8-4y+y²=0

2y²-4=0

2y²=4

y²=2

y=-√2 ∨ y=√2

x=2-√2 ∨ x=2+√2

 

2011-06-25T02:26:33+02:00

x-y = 2

x^2 - 4x + y^2 = 0

 

y = x-2

x^2 - 4x +(x-2)^2 = 0

 

x^2 - 4x + x^2 - 4x + 4 = 0

2x^2 - 8x + 4 = 0   I:2

x^2 - 4x + 2 = 0

D(delta) = 16 -8 = 8

VD = V8 = 2V2

 

x1 = (4-2V2)/2 = 2-V2

x2 = (4+2V2)/2 = 2+V2 

y1 = 2-V2-2 = -V2

y2 = 2+V2-2 = V2

 

{x1 = 2-V2}

{y1 = -V2}

 

{x2 = 2+V2}

{y2 = V2}